Fabrication of hybrid crosslinked network with buffering capabilities and autonomous strengthening characteristics for dental adhesives. (February 2018) - Song, Linyong; Ye, Qiang; Ge, Xueping; Misra, Anil; Tamerler, Candan; Spencer, Paulette
Graphical abstract: Abstract: Ingress of bacteria and fluids at the interfacial gaps between the restorative composite biomaterial and the tooth structure contribute to recurrent decay and failure of the composite restoration. The inability of the material to increase the pH at the composite/tooth interface facilitates the outgrowth of bacteria. Neutralizing the microenvironment at the tooth/composite interface offers promise for reducing the damage provoked by cariogenic and aciduric bacteria. We address this problem by designing a dental adhesive composed of hybrid network to provide buffering and autonomous strengthening simultaneously. Two amino functional silanes, 2-hydroxy-3-morpholinopropyl (3-(triethoxysilyl)propyl) carbamate and 2-hydroxy-3-morpholinopropyl (3-(trimethoxysilyl)propyl) carbamate were synthesized and used as co-monomers. Combining free radical initiated polymerization (polymethacrylate-based network) and photoacid-induced sol-gel reaction (polysiloxane) results in the hybrid network formation. Resulting formulations were characterized with regard to real-time photo-polymerization, water sorption, leached species, neutralization, and mechanical properties. Results from real-time FTIR spectroscopic studies indicated that ethoxy was less reactive than methoxy substituent. The neutralization results demonstrated that the methoxy-containing adhesives have acute and delayed buffering capabilities. The mechanical properties of synthetic copolymers tested in dry conditions were improved via condensation reaction of the hydrolyzed organosilanes. The leaching from methoxy containing copolymers was significantly reduced. The sol-gel reaction provided a chronic and persistent reaction in wet condition-performance that offers potential for reducing secondary decay and increasing the functional lifetime of dental adhesives. Statement of Significance: The interfacial gaps between the restorative composite biomaterial and the tooth structure contributes to recurrent decay and failure of the composite restoration. The inability of the material to increase the pH at the composite/tooth interface facilitates the outgrowth of more cariogenic and aciduric bacteria. This paper reports a novel, synthetic resin that provides buffering capability and autonomous strengthening characteristics. In this work, two amino functional silanes were synthesized and the effect of alkoxy substitutions on the photoacid-induced sol-gel reaction was investigated. We evaluated the neutralization capability (monitoring the pH of lactic acid solution) and the autonomous strengthening property (monitoring the mechanical properties of the hybrid copolymers under wet conditions and quantitatively analyzing the leachable species by HPLC). The novel resin investigated in this study offers the potential benefits of reducing the risk of recurrent decay and prolonging the functional lifetime of dental adhesives.